Does Business Intelligence Reverse the Negative Impact of ESG on Firm Value? - Oviliani Yenty Yuliana; Yenni Mangoting; Audrie Jessalyne Tankilisan; Eugunia Evanthe Yenardi; Desi Arisandi (Universitas Pendidikan Nasional, 2026)
Environmental degradation in Indonesia has increased significantly in recent decades, thereby increasing the importance of Environmental, Social, and Governance (ESG) factors in corporate decision-making. This study aims to analyse the impact of ESG implementation on company value and investigate the moderating effect of business intelligence (BI) on this relationship. This research uses data panels from 35 listed non-financial companies on the Indonesia Stock Exchange, covering the period from 2018 to 2023. A total of 201 observations were collected through purposive sampling. We used descriptive statistics and Fixed Effects regression methods to analyse the data using a data panel approach. The findings show that ESG implementation is associated with a decrease in firm value. This suggests that such initiatives were still perceived primarily as symbolic activities that imposed additional costs and responded to external pressures rather than being fully embedded in corporate strategy. BI, when considered independently, also exhibits a negative relationship with firm value. Nevertheless, the correlation between ESG and BI yields a positive impact, implying that effective BI governance enhanced the credibility and strategic relevance of ESG information. The combined effect appeared to strengthen market perceptions and supports long-term formation firm value. This study provides empirical insights regarding literature that discusses the inconsistent link on the relationship of ESG and firm value in developing countries and emphasizes the strategic role of BI as an information governance mechanism that can increase the relevance of ESG for investors.